2017
DOI: 10.12816/0038401
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Essential Oils on the Quality of UF-Soft Cheese During Storage

Abstract: The present study aimed to evaluate the chemical composition, antioxidant activity, antimicrobial properties and the minimum inhibitory concentrations (MICs) of three essential oils extracted from cumin, rosemary and thyme and their mixture and their effect on physicochemical, microbial, rheological and sensorial attributes of ultrafiltrated (UF)-soft cheese. UF-soft cheese was prepared from UF milk retentate with adding 0.1% of these essential oils. The results revealed that the different essential oils had r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
6
7
0
Order By: Relevance
“…The enhancement effect of REO addition on sensory properties in our study matched the findings reported by El-Kholy et al, as they showed that adding REO to ultra-filtrated soft cheese samples improved sensory characteristics, while the control samples had lower scores [34]. According to other findings, adding 0.14 g/L of REO to yogurt samples resulted in the best flavor, taste, and texture, whereas increasing the previous concentration resulted in the worst flavor, taste, and texture [15].…”
Section: Sensory Evaluationssupporting
confidence: 91%
See 3 more Smart Citations
“…The enhancement effect of REO addition on sensory properties in our study matched the findings reported by El-Kholy et al, as they showed that adding REO to ultra-filtrated soft cheese samples improved sensory characteristics, while the control samples had lower scores [34]. According to other findings, adding 0.14 g/L of REO to yogurt samples resulted in the best flavor, taste, and texture, whereas increasing the previous concentration resulted in the worst flavor, taste, and texture [15].…”
Section: Sensory Evaluationssupporting
confidence: 91%
“…The decline in protein content in our study after 8 days of storage could be attributed to proteolytic activity by added microorganisms (76). Our findings are consistent with the results of El-Kholy et al and Thabet et al [34,82].…”
supporting
confidence: 94%
See 2 more Smart Citations
“…According to the data, preventing the growth of E. coli, S. typhi, S. aureus, B. subtilis, B. cereus and A. niger on cheese. Thus, essential oils supplied an extension of shelf life and improvement for consumer perception [28]. Singh, Kapoor, and Singh (2011) established that the spoilage caused by bacteria was well controlled when anise EO and its oleoresin were added with yogurt at varying concentrations (0.1-1.0 g/L) [29].…”
Section: The Preservation Potential Of Eos In Food Systemsmentioning
confidence: 99%